Jaagsiekte Sheep Retrovirus Can Reach Peyer's Patches and Mesenteric Lymph Nodes of Lambs Nursed by Infected Mothers. (November 2016) - Borobia, M.; De las Heras, M.; Ramos, J. J.; Ferrer, L. M.; Lacasta, D.; De Martino, A.; Fernández, A.; Loste, A.; Marteles, D.; Ortín, A.
Ovine pulmonary adenocarcinoma (OPA) is a contagious lung cancer of sheep caused by jaagsiekte sheep retrovirus (JSRV). It is generally accepted that transmission by the respiratory route occurs under natural conditions. However recent studies strongly indicate that JSRV can also be transmitted to lambs perinatally via colostrum and milk (C/M). The aim of this work was to confirm that C/M can transmit JSRV infection to lambs under natural conditions and investigate the initial events associated with this transmission route. We have analyzed the presence of JSRV in C/M samples from 22 naturally infected, asymptomatic ewes throughout a lactation period, and in various tissues collected from a group of 36 of their lambs that were fed naturally. The lambs were euthanized at 12, 24, 48, and 72 hours and at 5 and 10 days after birth. We detected JSRV-provirus by PCR in the somatic C/M cells from 10/22 ewes (45.45%). The virus was also detected in 9/36 lambs (25%). JSRV-infected cells, with lymphoreticular-like morphology, were observed by immunohistochemistry (IHC) and in situ hybridization (ISH) in Peyer's patches (PP) from the small intestine of the youngest lambs and in mesenteric lymph nodes (MLN) from lambs older than 72 hours. The virus was also detected by PCR in white blood cells (WBC) in 2/36 lambs (5.5%). These results confirm colostral transmission of JSRV to lambs under natural conditions. Infected lymphoreticular cells contained in C/M appear to be involved. These cells can cross the intestinal barrier of newborn lambs, reach the MLN and enter into circulation.